2000
DOI: 10.1530/eje.0.1430471
|View full text |Cite
|
Sign up to set email alerts
|

A novel activating mutation in the thyrotropin receptor gene in an autonomously functioning thyroid nodule developed by a Japanese patient

Abstract: Objective: A number of activating mutations of the thyrotropin receptor (TSHR) have been found in autonomously functioning thyroid nodules (AFTNs) in European patients. We aimed to study TSHR mutation in AFTNs in Japanese patients because no TSHR activating mutation has been found by previous incomplete studies. Design: A typical AFTN developed in a 69-year-old Japanese woman was studied. Methods: The entire exon 10 of the TSHR cDNA was sequenced. Functional studies were done by sitedirected mutagenesis and tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 36 publications
3
22
0
1
Order By: Relevance
“…In contrast, it has been reported to be very low in Japan [23]. However, Kosugi et al analyzed the entire exon 10 of the TSHR gene and found the first activating mutation in the TSHR gene in a Japanese patient with AFTN [17]. Vanvooren et al consistently identified four mutations in the TSHR gene in 10 Japanese AFTN patients and thus suggested that activating mutations in the TSHR gene may not be rare in the Japanese population [18].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast, it has been reported to be very low in Japan [23]. However, Kosugi et al analyzed the entire exon 10 of the TSHR gene and found the first activating mutation in the TSHR gene in a Japanese patient with AFTN [17]. Vanvooren et al consistently identified four mutations in the TSHR gene in 10 Japanese AFTN patients and thus suggested that activating mutations in the TSHR gene may not be rare in the Japanese population [18].…”
Section: Discussionmentioning
confidence: 99%
“…Whereas we did not examine other exons of TSHR and Gsα genes, our results suggest that oncogenic mutations of these genes might not play a major role in the development of AFTN in Japan. Further studies on a larger number of AFTN patients are clearly required to determine the actual prevalence of gain-of-function mutations in the TSHR and Gsα genes in the Japanese population since previous studies have analyzed these mutations in only a small number of AFTN cases [17,18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The second example focuses on three tightly-packed triad-like interacting hydrophobic residues, which constitute a hydrophobic patch for stabilization of the basal TSHR conformation. Several naturally occurring single CAMs are known at these positions ( Figure 2B) and might be related to hyperfunctioning thyroid nodules (Alberti et al, 2001;Esapa et al, 1999;Gozu et al, 2006;Holzapfel et al, 1997;Kosugi et al, 2000;Trulzsch et al, 2001). Each of these CAMs causes disruption of the interacting triad, leading to constitutive TSHR activation.…”
Section: Linkage Between Structural and Functional Information Of Glymentioning
confidence: 99%